Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Pourquoi n'y-a-t-il pas eu de grands artistes femmes? - Nochlin, Linda (Femmes, art et pouvoir., 1993)
Keywords: approches et analyses; arts; cours; discipline; domination masculine; fem1000; histoire de l'art; histoire et politique; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; théories féministes

Frontiers: Selected essays and writings on racism and culture, 1984-1992 - Philip, Marlene Nourbese (Mercury Press, 1992)
Cette collection d'essais tant attendue se compose d'écrits sélectionnés parmi les nombreuses apparitions de la boursière Guggenheim Marlene Nourbese Philip dans des magazines, des journaux et des revues, y compris FUSE . Mordant, élégant, tour à tour farouchement interrogateur, magiquement lyrique et doucement explorateur, l'examen par Philip des questions contemporaines de race et de culture est toujours éloquent et impérieux.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; arts; cours; discipline; fem1000; inégalités; littérature; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; états-unis; études littéraires

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques